La voce e il fenomeno: da Husserl a Derrida e oltre - Trincia, Francesco Saverio (Bollettino Filosofico, 2021)
Ther essay aims to analyse and deconstruttively explain the “beyond” of the title. Moving from the the going beyond the husserlian first Logisch Untersuchung realized by Jacques Derrida in La voix et le phénomène, it becomes possible to understand the sense of this deconstrutive going beyond, first of all through the understanding of the crucial concept of difference as différance between expressive and significant sign, that is «index». The difference as différance allows at the same time their interconnection. The transcendental value of the «index» is cancelled by the reversal of the soliloquy of the conscience with itself in the «writing» («écriture»). The derridean interpretation of the unconscious in Sigmund Freud as an «originary suppement» is explained in La voix et le phénomène. It is also briefly analysed. Furthermore, the essays by Rudolf Bernet and Jocelyn Benoist and their ambivalent interpretation of Derrida’s phenomenology are examined. The essay ends with the decostructive reading of the last chapter of the book. Keywords: Benoist, Bernet, Differánce, Freud, Originary Suppement